Robespierre the man who divides us the most - Gauchet, Marcel 1946- (Princeton University Press, 2022)
How Robespierre's career and legacy embody the dangerous contradictions of democracyMaximilien Robespierre (1758-1794) is arguably the most controversial and contradictory figure of the French Revolution, inspiring passionate debate like no other protagonist of those dramatic and violent events of the late eighteenth century. The fervor of those who defend Robespierre the "Incorruptible," who championed the rights of the people, is met with revulsion by those who condemn him as the bloodthirsty tyrant who sent people to the guillotine. Marcel Gauchet argues that he was both, embodying the glorious achievement of liberty as well as the excesses that culminated in the Terror.In much the same way that 1789 and 1793 symbolize the two opposing faces of the French Revolution, Robespierre's contradictions were simply the contradictions of the revolution itself. Robespierre was its purest incarnation, neither the defender of liberty who fell victim to the corrupting influence of power nor the tyrant who betrayed the principles of the revolution. Gauchet shows how Robespierre's personal transition from opposition to governance was itself an expression of the tragedy inherent to a revolution whose own prophetic ideals were impossible to implement.This panoramic book tells the story of how the man most associated with the founding of modern French democracy was also the first tyrant of that democracy, and offers vital lessons for all democracies, for which the descent into tyranny is a perpetual danger
Keywords: HISTORY / Europe / France; Revolutionaries -- France -- Biography